EXPLORING THE LIVED EXPERIENCE OF RACIALIZED AGEISM AMONG OLDER ADULTS: A PHENOMENOLOGICAL STUDY. (20th December 2022) - Steward, Andrew; De Fries, Carson; Dunbar, Annie Zean; Trujillo, Miguel; Zhu, Yating; Nicotera, Nicole; Hasche, Leslie
Abstract: Ageism is a prevalent, insidious social justice issue which has harmful effects on the health of older adults. Preliminary literature explores the intersectionality of ageism with sexism, ableism, classism, and ageism experienced among LGBTQ+ older adults. To our knowledge, the intersection of ageism with racism, or racialized ageism, is largely absent from the literature. This qualitative study explored the following research question from a phenomenological perspective: "What is the lived experience of racialized ageism among diverse older adults?" Twenty participants 60+ years of age (M=69) in the U.S. Mountain West identifying as Black, Latino(a), Asian-American/Pacific Islander, Indigenous, or White engaged in a one-hour interview between February and July 2021. A three-cycle coding process used constant comparison methods. Five coders independently coded interviews, engaging in critical discussion to resolve disagreements. An audit trail, member checking, and peer debriefing enhanced credibility. Six umbrella themes and 20 sub-themes were identified. In this paper, the following six sub-themes are highlighted with direct implications for practice:1) compounding oppression, 2) being avoided or categorized due to others' discomfort, 3) increased disrespect, 4) microaggressions, 5) acts of hate, and 6) cultural values/respect for elders as a protective factor. Implications include informing how practitioners may enhance support for older adults in preventing and coping with experiences of racialized ageism. Enhanced understanding of racialized ageism should also inform existing anti-ageism initiatives at the community level. Future research should focus on the experience of racialized ageist microaggressions and the relationship between racialized ageism and specific health outcomes.